Biliopancreatic Endoscopy Practical Application (Springer Singapore, 2018)
This book aims to provide the basic technology and recent advances in biliopancreatic endoscopy. The method of Endoscopic retrograde cholangiopancreatography (ERCP) is popularly applied to enlarge the papillary orifice for removal of biliary and pancreatic stones, to relieve obstruction of distal bile duct or pancreatic duct by nasobiliary / nasopancreatic drainage or stenting, and to remove the premalignant tumor of papilla in recent four decades. The diagnostic role of ERCP is already replaced by the noninvasive images such as abdominal sonography, computed tomography, magnetic resonance cholangiopancreatography (MRCP) and endoscopic ultrasonography (EUS). This book will be contributed by the senior members of the Digestive Endoscopy Society of Taiwan (DEST) who are the leading ERCPists of the medical centers and teaching hospitals in Taiwan. There are 21 chapters, including the various techniques of therapeutic ERCP and EUS, how to approach the difficult cases and prevent complications. Recently, many new facilities and techniques develop to solve the difficult problems, but those new methods may have potential hazard to the patients, particularly in the inexperienced hands. We will share our clinical experience and comments on the recent literatures, to illustrate the standard operative procedures of biliopancreatic endoscopy, and focus on the patients' safety as well as efficacy. We hope this book will be helpful for the readers in clinical application and facilitate the junior doctors to choose the cost-effective and safe procedure to help their patients in the future.